2023
DOI: 10.1093/plcell/koad289
|View full text |Cite
|
Sign up to set email alerts
|

Thermoprotection by a cell membrane–localized metacaspase in a green alga

Yong Zou,
Igor Sabljić,
Natalia Horbach
et al.

Abstract: Caspases are restricted to animals, while other organisms, including plants possess metacaspases (MCAs), a more ancient and broader class of structurally related yet biochemically distinct proteases. Our current understanding of plant MCAs is derived from studies in streptophytes, and mostly in Arabidopsis (Arabidopsis thaliana) with nine MCAs with partially redundant activities. In contrast to streptophytes, most chlorophytes contain only one or two uncharacterized MCAs, providing an excellent platform for MC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…In higher plants, metacaspases are localized mainly in the cytosol and the nucleus, but are also found in mitochondria, the cell wall and the apoplast (Huh, 2022). Recent data suggest the localization of CrMCA-II at the plasma membrane and its translocation to the cytosol during heat stress (Zou et al, 2023). In contrast, in overexpression lines, CrMCA-II was observed in the cytosol during control conditions, while the CrMCA-I signal was restricted at the mitochondria (Lambert et al, 2023).…”
Section: Degradomes Of the Type I And Type Ii Metacaspases In C Reinh...mentioning
confidence: 99%
See 3 more Smart Citations
“…In higher plants, metacaspases are localized mainly in the cytosol and the nucleus, but are also found in mitochondria, the cell wall and the apoplast (Huh, 2022). Recent data suggest the localization of CrMCA-II at the plasma membrane and its translocation to the cytosol during heat stress (Zou et al, 2023). In contrast, in overexpression lines, CrMCA-II was observed in the cytosol during control conditions, while the CrMCA-I signal was restricted at the mitochondria (Lambert et al, 2023).…”
Section: Degradomes Of the Type I And Type Ii Metacaspases In C Reinh...mentioning
confidence: 99%
“…In C. reinhardtii, mutant strains of CrMCA-I and CrMCA-II were treated with GSNO to induce oxidative stress and only the CrMCA-II mutant was able to prevent PCD (Lambert et al, 2023). However, in a different study, CrMCA-II mutant cells were shown to be sensitive to heat stress (Zou et al, 2023). Contradictions in the tolerance and viability of the metacaspase mutants denote the complex underlying mechanisms of cellular stress response and the potential multifunctionality of metacaspases.…”
Section: Differential Expression and Stress Tolerance Of Metacaspasesmentioning
confidence: 99%
See 2 more Smart Citations
“…In turn, the type I metacaspase MC1 participates in clearance of harmful protein aggregates formed as a result of proteotoxic stress, a function conserved from fungi to plants (Lee et al ., 2010; Coll et al ., 2014; Hill et al ., 2014; Ruiz‐Solaní et al ., 2023). On the other hand, both Arabidopsis MC3 and Chlamydomonas CrMCA‐II have been shown to be involved in drought and heat stress tolerance, respectively, independent of their catalytic activity (Pitsili et al ., 2023; Zou et al ., 2023). Collectively, despite the fact that metacaspases may have evolved from the same ancestor as caspases, current evidence indicates that they are not simply executioner caspases in the context of PCD and that they could instead function, or have additional, context‐dependent roles, as pro‐survival proteins.…”
Section: A Vision For the Next Decade Of Plant Pcd Researchmentioning
confidence: 99%